Are perceptions of grandparenthood related to family and life satisfaction? A study with emerging adults. (April 2021) - Miguel, Isabel; Araújo, Alexandra M.; Fernandes, Sandra; Carneiro, Luísa; Fernandes, Paula
Given the crucial role that grandparents play in the upbringing and well-being of their grandchildren, research regarding the perceived importance of grandparents for their emerging adult grandchildren is of particular relevance. This study examined the relations between perceived grandparents' roles and family and life satisfaction in Portuguese emerging adults. Participants (N = 387), aged 18–25, completed a structured self-report questionnaire. Findings of structural equation modeling showed that emerging adults' perceptions of grandparental roles of counselor, enjoying the relationship, and indulgence are positively related to their family and life satisfaction. The mediation analysis showed that family satisfaction mediated the relation between perceptions of grandparents acting as counselors and the life satisfaction of emerging adult grandchildren. Implications of family relationships and grandparenting in the context of emerging adulthood are discussed.